Policy Feedback How Policies Shape Politics - Béland, Daniel (Social Sciences, 2022)
This element explores early and more recent contributions of the policy feedback literature to clarify the meaning of this concept and its contribution to both political science and policy studies. This element also discusses the practical implications of policy feedback research through a discussion of its potential impact on policy design.